A Textual and Contextual Examination of Social Inclusiveness and Education in Q. 'Abasa (80): 1-10 - Irwan Ahmad Akbar; Imad Syauqi (LPPM Universitas KH. A. Wahab Hasbullah, Jombang, Indonesia, 2025)
This research explores the educational values within Surah ‘Abasa (80):1-10 through the lens of classical and modern Tafsir, aiming to uncover its relevance to Islamic pedagogical principles. The study employs a qualitative methodology, utilizing primary Tafsir sources such as Tafsir al-Thabari, Tafsir al-Qurthubi, and Tafsir al-Misbah to provide a comprehensive analysis of the text. The findings reveal that Q. 80:1-10 emphasizes non-discrimination in education, advocating for equal treatment of all students, regardless of their physical abilities or social backgrounds. It promotes the philosophy of universal education, stressing education as both a right and a duty. The study underscores the principle of non-segregation and suggests that obstacles to education are more influenced by external factors than intrinsic limitations. The implications of these findings suggest a need for inclusive educational policies and practices that ensure equitable access to learning for all students. This research contributes to the discourse on Islamic education by highlighting the significance of inclusivity and fairness as foundational elements of educational frameworks in Muslim societies, particularly Indonesia.